Effects of (1E, 4E)-2-Methyl-1, 5-bis(4-nitrophenyl)penta-1, 4-dien-3-one on Trypanosoma cruzi and Its Combinational Effect with Benznidazole, Ketoconazole, or Fluconazole. (23rd May 2017) - Peron, Francieli; Lazarin-Bidóia, Danielle; Ud Din, Zia; Rodrigues-Filho, Edson; Ueda-Nakamura, Tânia; Silva, Sueli de Oliveira; Nakamura, Celso Vataru
Abstract : This study reports the activity induced by (1 E, 4 E )-2-methyl-1, 5-bis(4-nitrophenyl)penta-1, 4-dien-3-one (A3K2A3) against Trypanosoma cruzi. This compound showed trypanocidal activity against the multiplicative epimastigote and amastigote forms of this protozoan, with IC50 values of 1.99 ± 0.17 and 1.20 ± 0.16 μ M, respectively, and EC50 value of 15.57 ± 0.34 μ M against trypomastigotes. The combination of A3K2A3 with benznidazole or ketoconazole demonstrated strong synergism, increasing effectiveness against trypomastigotes or epimastigotes of T. cruzi . In addition, the drug combination of A3K2A3 with benznidazole or ketoconazole on LLCMK2 cells demonstrated an antagonist effect, which resulted in greater protection of the cells from drug damage. The combination of the compound with fluconazole was not effective. Transmission and scanning electron micrographs showed changes on parasites, mainly in the cytoplasmatic membrane, nucleus, mitochondrion, and Golgi complex, and a large increase in the number of autophagosome-like structures and lipid-storage bodies, accompanied by volume reduction and rounding of the parasite. A3K2A3 might be a promising compound against T. cruzi .